Child with diphtheria pertussis and tetanus induced afebrile seizures - Sonawane, Vijay B.; Kotrashetti, V.; Bainade, Kapil; Nair, Shweta; Gupta, Samarth (International Journal of Contemporary Pediatrics, 2020)
Current childhood vaccines are safe and effective but diphtheria pertussis and tetanus vaccine (DPT) has been considered to be one of the most reactogenic. The adverse reactions after immunization with adsorbed DPT vaccine have been widely debated and publicized. The conventional whole cell pertussis vaccines expected to give certain minor and local reactions as it contains lipopolysaccharide and active pertussis toxin (PT). Reactions occurring after DPT vaccine have been described mostly to the pertussis component of the vaccine. Vaccination with diphtheria and tetanus toxoids and whole cell pertussis, DPT vaccine was associated with a risk of seizures and encephalopathy.